The effectiveness of e-procurement system in reducing lobbyist involvement in public procurement / Jamaliah Said, Marlina Wati Ishak and Normah Omar - Said, Jamaliah; Ishak, Marlina Wati; Omar, Normah (Universiti Teknologi MARA Cawangan Selangor, 2017)
Corruption represents a major leakage of public fund in many countries in the world. It has been highlighted that the involvement of unnecessary lobbying in the procurement contributes to the corruption. As a result, the Malaysian government has introduced the E-Procurement System to improve its services and to promote transparency in the procurement processes. This study aims to assess the effectiveness of the E-procurement system in reducing the lobbyist involvement in one of the largest statutory bodies in Malaysia. For this qualitative study, five procurement officers and three suppliers who had been using the system since it was implemented in the year 2011 were interviewed. Document review was also performed to access information on the processes in the system in support of the feedback from the respondents. The interview results showed that the E-procurement system was effectively implemented in largest statutory body (ACED) and reduced the involvement of lobbyist in the procurement processes. Both groups of informants agreed that the E-procurement system was an effective mechanism to curb procurement fraud because the processes were automated and transparent at every stage. Each process was conducted by a different person and it promoted integrity and transparency in the system. The E-Procurement System was found to be effective in preventing direct communication between the procurement officers and suppliers, therefore reducing the risk of lobbying. The E-procurement System was also bound by specific laws and regulations governing both parties, to which they must comply. The present study concludes that the system can reduce the unethical behaviour by lobbyist and that it should be implemented.